KEPEMIMPINAN TRANSFORMASIONAL DALAM KONTEKS KEPEMIMPINAN KRISTEN - Adri Tanga Pauwang; Yelmi Nino, Windi Kala' Liling, Selpianty Rombe, Diana Ripa (CV. ADIBA AISHA AMIRA, 2024)
Transformational leadership, the primary focus of leadership research, is recognized for its potential to bring about positive changes in individuals and organizations. In the context of Christian leadership, where spiritual and moral values dominate, this study explores the effective integration of transformational leadership principles. Through a literature review, the research aims to develop a holistic understanding of transformational leadership in Christian leadership, identifying current perspectives and findings through an examination of academic literature. The method involves selecting literature based on inclusion criteria related to transformational leadership and the Christian context, with an in-depth analysis of findings and researchers' perspectives. The results indicate that transformational leadership in the Christian context reflects a unique pattern, where Christian values such as love, service, and integrity are the primary drivers of leaders' motivation. Christian leaders applying this model tend to motivate through spiritual aspects, guide for spiritual growth, and promote community service as integral to leadership. These findings provide a crucial foundation for understanding transformational leadership in Christian communities, with significant implications for leadership concept development and potential further research on its practical implementation